IMPLEMENTATION OF THE PROJECT-BASED DIFFERENTIATED LEARNING MODEL IN SCIENCE AND SOCIAL SCIENCES (IPAS) - Izzul Haq, Muhammad Rifqi; Arifin, Moch. Bahak Udin By (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
Abs Research on the Application of Project-Based Differentiated Learning Models in Natural Sciences and Social Sciences (IPAS) Learning is motivated by the low percentage of student learning success and low student creativity in learning. So, this research was prepared to find out how to implement and effectively apply the project-based differentiation learning model in science and science learning. This research was carried out during two meetings starting on 28 October 2023 and 31 October 2023, with a research population of class IV students at MI Muhammaddiyah 2 Kedungbanteng Tanggulangin totaling 18 students, consisting of 10 male students and eight female students. The method used by researchers is a one-group pretest-posttest quantitative experimental method. From the research results, the average student pretest score was 59.6%, and the average student posttest score was 70.8%. It can be concluded that the implementation and effectiveness of the Project Based Learning Differentiated learning model is better compared to direct science and social studies learning (IPAS).